SOSIALISASI DAN PROMOSI : PENCEGAHAN MASALAH KESEHATAN JIWA MATERNAL GUNA MENCIPTAKAN BUMIL SEHAT DI MASA PANDEMI - Cintika Yorinda Sebtalesy; Anisia Widyaningrum, Dian (LPPM STIKES Madani, 2022)
ABSTRACT The current COVID-19 pandemic has become a worldwide concern, including in Indonesia and has caused several health problems in several vulnerable groups, one of which is pregnant women. The fear of going to a health facility for a pregnancy check causes pregnant women to feel anxious about the condition of their fetus. In an era full of physical distancing restrictions during the COVID-19 pandemic as it is now, the support system that usually promotes mental health during the vulnerable period of transition to becoming a mother from family and loved ones is very likely to be reduced or even lost. Many have reported more anxiety about pregnancy problems amid the pandemic, likely due to concerns about the virus. This makes pregnant women more at risk for mental health problems. The purpose of this community service is to socialize and promote the prevention of maternal mental health problems in order to create healthy pregnant women during the pandemic. The method of implementing this community service consists of three stages, namely the preparation, implementation, and evaluation stages. At the implementation stage, socialization and promotion were given to prevent mental health problems during the COVID-19 pandemic. As a result of community service, pregnant women have gained good knowledge about how to prevent maternal mental health problems during the COVID-19 pandemic. Health socialization and promotion to improve mental health of pregnant women is recommended to be carried out as a form of collaboration between the Health Service and the local government as well as with the support of the main family, husband and parents so as to create mentally healthy pregnant women during the COVID-19 pandemic.